Exercices sur la règles des parenthèses

1
[x + 7 - (2 + x)] + (8 - x - 2) =
Solution
2
(x + 3 - y -6) - [7 + x + (3 - x)] =
Solution
3
[(3 - a) - (b - a + 2)] - [7 - b - (a + 2)] =
Solution
4
[(8 - b - 5) - (12 - a)] + [(a + 3 - a - 5) - (10 - b)] =
Solution
5
(a - 1,2 + b - 1,8) - [7 - a + (3,7 + a - b - 5,7)] =
Solution
6
[2,3 - x - (y - x) + (1,7 + y - z)] - (1,4 + x + y -2,4) =
Solution
7
[(z - 3,6 - y + 1,6) - (y + z - y - 1)] + [(x - 1) - (x - 2)] =
Solution
8
[(2 - a - 3) - (a + b - 3 - b)] - [(a - 1) - (a - 2) - (a - 3)] =
Solution
9
[(1,5 - b + c - 0,5) - (b + c - b)] - [(1 - c) - (2,5 + c) - (0,5 + c)] =
Solution
10
[(x + y - x - 1) + (1 - y - 2)] + [(z - 3) - (1 - z) - (z + 1)] =
Solution

Retour